Synthesis and characterization of poly(sodium-p-styrenesulfonate)/modified SiO2 spherical brushes - N. Su; H. B. Li; H. M. Zheng; S. P. Yi; X. H. Liu (eXPRESS Polymer Letters, 2012)
The multistep procedures for preparing novel anionic spherical polyelectrolyte brushes (ASPB) by grafting sodium-p-styrenesulfonate (SSS) from the surface of γ-methacryloxypropyl trimethoxy-silane modified SiO2 nanoparticles were demonstrated. The morphology of ASPB was characterized by Transmission Electron Microscopy (TEM) and Scanning Electron Microscopy (SEM). The core radius Rc and hydrodynamic radius Rh of ASPB measured by Zeta Potential/Particle Sizer (ZLS) were ca. 50nm and (84.5±1) nm respectively. The percentage of grafting (PG%) of polyelectrolyte brushes was 4.3% investigated by Thermo-gravimetric analysis (TGA). Detailed characterizations on ASPB were performed by cleaving the grafts from the anchoring surface. The molecular weight (MW) and polydispersity (MW/Mn) of brushes were 1.788•103 g/mol and 1.6 respectively from Gel Permeation Chromatography (GPC) measurements. Moreover, Rh and ζ-potential of ASPB in the presence of aqueous NaCl solutions of different concentrations were discussed.